2003
DOI: 10.1073/pnas.0537286100
|View full text |Cite
|
Sign up to set email alerts
|

Type I polyketide synthase requiring a discrete acyltransferase for polyketide biosynthesis

Abstract: Type I polyketide synthases (PKSs) are multifunctional enzymes that are organized into modules, each of which minimally contains a ␤-ketoacyl synthase, an acyltransferase (AT), and an acyl carrier protein. Here we report that the leinamycin (LNM) biosynthetic gene cluster from Streptomyces atroolivaceus S-140 consists of two PKS genes, lnmI and lnmJ, that encode six PKS modules, none of which contain the cognate AT domain. The only AT activity identified within the lnm gene cluster is a discrete AT protein enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
262
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(266 citation statements)
references
References 32 publications
0
262
0
4
Order By: Relevance
“…Unlike NRPS-like enzymes (37,38), these type IIlike NRPS clusters have a complete core domain set, such as the identified putative brucebactin gene clusters that contain one fully dissociated NRPS module. Previously, reclassification of PKSs had been proposed (39), due to the discoveries of transition states between type I and II PKSs, the trans-AT PKS systems (25), and that between type II and III PKSs shown to be independent of the acyl carrier protein (40). The type II-like PKS clusters found in this study also appeared as transition states between type I and type II PKSs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Unlike NRPS-like enzymes (37,38), these type IIlike NRPS clusters have a complete core domain set, such as the identified putative brucebactin gene clusters that contain one fully dissociated NRPS module. Previously, reclassification of PKSs had been proposed (39), due to the discoveries of transition states between type I and II PKSs, the trans-AT PKS systems (25), and that between type II and III PKSs shown to be independent of the acyl carrier protein (40). The type II-like PKS clusters found in this study also appeared as transition states between type I and type II PKSs.…”
Section: Discussionmentioning
confidence: 53%
“…S3). For example, a total of 113 bacterial gene clusters were found with free-standing acyltransferases (AT), which iteratively load the monomers in trans for other modular PKSs lacking an AT domain (25). They are almost all the hybrid type, illustrated by the fact that their docking and dehydratase domains are entirely from hybrid clusters (Fig.…”
Section: Gene-cluster Composition Reveals High Diversity Of Nrps and Pksmentioning
confidence: 99%
“…The use of a tailoring enzyme in trans for the formation of the naphthalene ring during polyketide chain extension is unprecedented in polyketide biosynthesis. To date, a number of unusual examples have been reported in PKS systems, in which the acyltransferase domain is located outside the PKS modules and functions in trans with the modular enzymes (Cheng et al, 2003;Piel, 2002). However, there are no examples of an oxidation reaction that takes place during polyketide chain assembly nor of an oxidation domain located within a modular PKS system.…”
Section: Discussionmentioning
confidence: 99%
“…Iterative type III PKS, also called chalcone synthases, are ACP-independent consisting of a single KS protein catalyzing multiple decarboxylative condensations (20). Rather recently, several bacterial PKS have been found that do not fit these model systems (21)(22)(23)(24)(25). For example, several iterative PKS have been discovered that contain one module located on a single protein analogous to fungal PKSs, and many of these PKS have been functionally characterized in heterologous hosts (26)(27)(28)(29).…”
mentioning
confidence: 99%